2017
DOI: 10.1002/pd.5045
|View full text |Cite
|
Sign up to set email alerts
|

Fetal left-sided cardiac structural dimensions in left-sided congenital diaphragmatic hernia - association with severity and impact on postnatal outcomes

Abstract: We identified associations between smaller fetal left-sided cardiac structural dimensions and classic CDH indices. Smaller aortic valve z-score was associated with iNO use; however, left heart dimensions showed no association with extracorporeal membrane oxygenation or mortality. Further study into the impact of left-sided hypoplasia on outcomes in CDH is worthy of evaluation in a larger, prospective study. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Another study, which evaluated cardiac dimensions in CDH, found no difference in LV:RV length ratio and showed normalization of ventricular size after postnatal diaphragmatic repair . Recently, smaller left‐side structures were associated with liver herniation and postnatal outcomes such as the use of nitric oxide in this population . None of these studies have evaluated longitudinal function of the fetal heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study, which evaluated cardiac dimensions in CDH, found no difference in LV:RV length ratio and showed normalization of ventricular size after postnatal diaphragmatic repair . Recently, smaller left‐side structures were associated with liver herniation and postnatal outcomes such as the use of nitric oxide in this population . None of these studies have evaluated longitudinal function of the fetal heart.…”
Section: Discussionmentioning
confidence: 99%
“…In left‐sided CDH fetuses, previous studies have demonstrated a prenatal left ventricular (LV) “smallness” secondary to heart compression by the abdominal herniated organs, but postnatal data have reported normal heart growth after neonatal surgical correction . Previous studies have attempted to evaluate fetal cardiac function in CDH, demonstrating decreased left cardiac output, normal shortening fractions, higher LV strain values, and smaller left heart structures, regardless of the side of the hernia . These cardiac function parameters could eventually be useful in establishing CDH severity, predicting perinatal death or the degree of neonatal pulmonary hypertension, and could even aid identifying those fetuses with better response to fetal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Strict criteria for new centers to join apply, so that reproducible lung assessment as well as safety is ensured . Meanwhile research is ongoing on comprehensive assessment of fetuses with isolated CDH, both in terms of predicting lung hypoplasia, pulmonary hypertension, and cardiac function . An increasing number of studies on fetal MR demonstrate how widespread this methodology is, whereas its superiority continues to be uncertain …”
Section: Fetal Surgerymentioning
confidence: 99%
“…Congenital diaphragmatic hernia (CDH) affects approximately 1 out of 2500 live births and results in herniation of abdominal contents into the thoracic cavity during fetal development, which effects pulmonary parenchymal and vascular development . Pulmonary hypoplasia and pulmonary hypertension remain the largest determinants of morbidity and mortality in the CDH population …”
Section: Introductionmentioning
confidence: 99%
“…Secondary effects of CDH result in changes to fetal circulatory physiology that alter cardiac preload and afterload which can lead to left heart hypoplasia (LHH) . Patients with isolated left‐sided CDH are shown to have smaller left heart dimensions in fetal life, and LHH has been associated with CDH severity . Left heart hypoplasia in CDH is believed to be secondary to both volume unloading of the left heart and external compression from herniated abdominal contents .…”
Section: Introductionmentioning
confidence: 99%